Föreställningar om klass och kön i Arbetsförmedlingens yrkesbeskrivningar? (Sociologisk Forskning, 2014)
Notions of Class and Gender in the Employment Service Job DescriptionsThis article examines whether job descriptions emphasize different characteristics and competences depending on the occupations’ social class and gender relations. The study is partly a replication of a similar analysis conducted by Gesser in the 1970s. The purpose is to examine the prevalence of stereotypes in occupational descriptions provided by the Swedish state, and if the descriptions contribute to class and gender labeling of occupations and, by extension, its practitioners. Previous research has shown that career guiding materials are characterized by notions of the appropriate practitioner’s class and gender. In this study we depart from the concept of doxa and argue that stereotypical images of occupations are based on common sense that remains unquestioned. The study draws on a quantitative content analysis of 420 job descriptions analyzed by various statistical methods. The overall results show that there are systematic differences. In general, social class seems to have greater impact than gender on what kind of competences that are emphasized in the descriptions. Social skills are emphasized in female dominated occupations, while physical abilities are highlighted in male-dominated occupations. To some extent, these results are uncontroversial, as it also portraits abilities necessary to do the work in different kind of occupations